Reviving the Case for GDP-Indexed Bonds - Borensztein, Eduardo (IMF Policy Discussion Papers; Policy Discussion Paper, 2002)
This paper seeks to revive the case for countries to self-insure against economic growth slowdowns by issuing GDP-indexed bonds. We simulate the effects of GDP-indexed bonds under different assumptions about fiscal policy reaction functions and their output effects and find that they could substantially reduce the likelihood that debt/GDP paths become explosive. The insurance premium would likely be small, because cross-country comovement of GDP growth rates is low and cross-country GDP growth risk is thus largely diversifiable for an investor holding a portfolio of GDP-indexed bonds. Potential obstacles to the emergence of a market for these bonds include the verifiability of GDP data, the trade-off between insurance and moral hazard, and the need for liquidity. The paper discusses institutional fixes and suggests an approach to attempting to start up a market.